RELATIONSHIP RELATIONSHIP BETWEEN COMPLETENESS OF DIAGNOSIS WRITING AND THE ACCURACY OF INJURY CASE CODEFICATION OF INPATIENTS AT RAA SOEWONDO PATI REGIONAL HOSPITAL: HUBUNGAN KELENGKAPAN PENULISAN DIAGNOSIS DENGAN KETEPATAN KODEFIKASI KASUS CEDERA PASIEN RAWAT INAP DI RSUD RAA SOEWONDO PATI - Kafida Mey Dhani Rahmat; Ambarwati; Hosizah Markam; Mieke Nurmalasari (Journal Health Information Management Indonesian, 2025)
The completeness of the medical record is very important, especially on the medical resume sheet which contains a summary of the patient's diagnosis. The completeness of the medical record greatly affects the accuracy of the disease codification. This study aims to determine the relationship between the completeness of writing a diagnosis and the accuracy of the coding of cases of injury to inpatients. This research is an analytical survey research with a quantitative approach. The study population was 94 medical records so that a sample of 49 medical records was obtained using a systematic random sampling technique. Data analysis of this study used the chi square test with a cross-sectional research design. The percentage of completeness in writing the diagnosis was 46.9% complete while 53.1% was incomplete. The accuracy of the codeification of injury cases is 36.7% correct and 63.3% is incorrect, while the percentage of external cause coding is 0% because there is no external cause coding by the officer. Fishers exact test showed that the value of p = 0.000 0.05. This means that H1 is accepted and Ho is rejected so that there is a relationship between the completeness of writing a diagnosis and the accuracy of the codefication of inpatient cases of injury at the RAA Soewondo Pati Hospital. The author suggests that there is communication between the medical record officer and doctors and nurses in order to write down the complete diagnosis and supporting information about the external cause in the case of injury, the coder is obliged to provide an external cause code in the case of injury and revision of the SOP regarding the provision of a diagnosis code